2004
DOI: 10.1086/422002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Intestinal Tract as a Reservoir and Source for Transmission of Nosocomial Pathogens

Abstract: The intestinal tract provides an important reservoir for many nosocomial pathogens, including Enterococcus species, Enterobacteriaciae, Clostridium difficile, and Candida species. These organisms share several common risk factors and often coexist in the intestinal tract. Disruption of normal barriers, such as gastric acidity and the indigenous microflora of the colon, facilitates overgrowth of pathogens. Factors such as fecal incontinence and diarrhea contribute to the subsequent dissemination of pathogens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
296
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(308 citation statements)
references
References 27 publications
6
296
1
5
Order By: Relevance
“…22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo. A sample of VRE isolates collected from our hematologyoncology unit during our study period was found to be primarily clonal by pulsed-field gel electrophoresis analysis (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo. A sample of VRE isolates collected from our hematologyoncology unit during our study period was found to be primarily clonal by pulsed-field gel electrophoresis analysis (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have revealed that the animal digestive tract is a reservoir for many nosocomial pathogens (Donskey 2004;Pond et al 2006), and this may be the same to yellow catfish. In this study, potentially opportunistic pathogens, such as Isolates SC3 (most related to SC53 SM28 SM31 SM8 SC51 SM42 SC37 SC63 SC52 SC20 SC61 SC3 PSC6 SC32 SC12 SM17 SC30 SC34 SC8 SC13 SC22 SC28 SC1 SC26 SC57 SC24 SC38 PSC19 SM13 SM22 SM30 PSC8 SM41 SC39 SM37 SM43 SC7 SM9 SC48 PSC2 PSC15 SC15 PSM3 SC36 SC54 SC21 SC27 PSC20 PSC1 PSM1 SC3 SM5 SM18 SM26 SC58 Chloroflexi SC23 SC4 SC59 SM3 SM20 SM44 SC11 SC42 SC45 SC10 SC49 SC14 SC44 SC60 SC5 Bootstrap values based on 1,000 re-samplings display the significance of the interior nodes, and are shown at branch points.…”
Section: Discussionmentioning
confidence: 98%
“…Colonization often precedes subsequent infection; consequently, "colonization pressure" is a critical term and unique for each kind of pathogen ( [Bonten et al, 1998] and [Donskey, 2004]). For vancomycin-resistant enterococci, the ratio of colonization to infection is quite high, meaning a single patient with a vancomycin-resistant enterococci (VRE) infection corresponds to a larger number of colonized persons surrounding the index patient and the more patients are colonized, the higher is the risk of an increasing number of infected patients ( [de Regt et al, 2008] and [Olivier et al, 2008]).…”
Section: Introductionmentioning
confidence: 99%